2018
DOI: 10.1007/s40264-018-0665-z
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis-Related Fractures in HIV-Infected Patients Receiving Long-Term Tenofovir Disoproxil Fumarate: An Observational Cohort Study

Abstract: IntroductionPatients with HIV infection may have a higher prevalence of osteoporosis and osteopenia, as well as an increased risk of bone fracture compared with non-HIV-infected individuals. Antiretroviral therapy is thought to be one of factors associated to osteoporosis-related bone fractures.ObjectiveThe aim of this study was to assess the effects of long-term exposure to tenofovir disoproxil fumarate (TDF) on the cumulative risk of osteoporosis-related bone fractures in Japanese patients with HIV infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
3
8
0
Order By: Relevance
“…Bone mineral density screening has been suggested for male patients with HIV infection older than 50 years and in postmenopausal women (Aberg et al, 2014;Gonciulea et al, 2017). In agreement with our results, previous study findings reveal that bone loss is observed in patients with HIV infection who receive ART (Mccomsey et al, 2008;Duvivier et al, 2009;Van Vonderen et al, 2009;Haskelberg et al, 2012;Grant et al, 2016;Hoy et al, 2017;Komatsu et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Bone mineral density screening has been suggested for male patients with HIV infection older than 50 years and in postmenopausal women (Aberg et al, 2014;Gonciulea et al, 2017). In agreement with our results, previous study findings reveal that bone loss is observed in patients with HIV infection who receive ART (Mccomsey et al, 2008;Duvivier et al, 2009;Van Vonderen et al, 2009;Haskelberg et al, 2012;Grant et al, 2016;Hoy et al, 2017;Komatsu et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Our results demonstrated that patients receiving NRTIcontaining regimen had a higher risk of osteoporosis. Studies have reported that NRTI-containing regimens, including zidovudine-lamivudine combination therapy and tenofovir monotherapies, induce osteoporosis or osteoporotic fractures (Van Vonderen et al, 2009;Haskelberg et al, 2012;Grant et al, 2016;Komatsu et al, 2018). Furthermore, our study showed that patients receiving zidovudine-lamivudine combination, lamivudine-abacavir combination, and abacavir had a higher risk of osteoporosis.…”
Section: Discussionsupporting
confidence: 54%
“…ART-exposed WWH vs MWH are at significantly greater risk of osteoporotic fracture [ 32 ]. Among ART-naive PWH initiating TDF, WWH had a 3 times greater fracture rate than MWH, and first osteoporotic fracture occurred sooner among women than men (123 vs 1438 days, respectively) [ 32 ].…”
Section: Hiv-associated Non-aids Comorbiditiesmentioning
confidence: 99%
“…ART-exposed WWH vs MWH are at significantly greater risk of osteoporotic fracture [ 32 ]. Among ART-naive PWH initiating TDF, WWH had a 3 times greater fracture rate than MWH, and first osteoporotic fracture occurred sooner among women than men (123 vs 1438 days, respectively) [ 32 ]. Another study including adult PWH showed that while MWH had a 1.5 times higher incident fracture rate compared with WWH from ages 36 to 46 years, the difference by sex diminished in older age groups [ 33 ].…”
Section: Hiv-associated Non-aids Comorbiditiesmentioning
confidence: 99%
“…Loss of BMD is one of the major side effects that have been observed since its development [155]. The relationship between bone diseases (osteoporosis and fracture) and TDF has been well documented in several clinical studies of patients co-infected with HIV and treated with HBV therapy [156]. The TDF-induced decrease in BMD is mainly observed in the hip and spine [157].…”
Section: Special Clinical Considerationsmentioning
confidence: 99%